Novas traduções da elegia erótica romana sob crítica - Oliveira, Luiza Wanderley Miranda de (2023)
The following research has two objectives: 1- to criticize recent translations of the roman erotic elegy by using Antoine Berman’s (1995) methodology – namely, the one made by Guilherme Gontijo Flores to the Sextus Propertius’ Elegies ([2014] 2019); the one by Guilherme Horst Duque to the Publio Ovidius Naso’s Amores (2015); and the one written by João Paulo Matedi Alves to the Tibullus’ Elegies (2014); 2- verify the construction of a school of translation, parting from an investigation of the tendency of translating the elegiac couplet with verses of twelve and ten syllables over time, from the reading of Carvalho’s essay (2005) and from interviews with the translators. For that we shall use the thoughts of Walter Benjamin (1921), Antoine Berman (1995; 2007), Haroldo de Campos (2011), João Angelo Oliva Neto (2015) and Raimundo Carvalho (2005).